ANALISIS PENGARUH KUALITAS PELAYANAN WEBSITE E-COMMERCE TERHADAP KEPUASAN KONSUMEN DAN NIAT BERPERILAKU LOYAL (STUDI KASUS PADA PERUSAHAAN ARISTYA SILVER, PENDAHULUAN E-commerce merupakan suatu tindakan melakukan transaksi bisnis secara elektronik den - Putu Agus Octa Aristya; Ni Putu Cempaka Dharmadewi Atmaja (STIMI Handayani Denpasar, 2016)
The purpose of this research is to know if there is any effect of the servicequality website E-commerce upon the consumers satisfaction. Next, is that to knowwhether not there is an effect upon the consumers behavioural loyalty intentions,and to know if there is also an effect in the service quality of the E-commerce websiteupon the consumers behavioural loyalty intentions to the Aristya Silver company.population in this research is that the online/E-customers, themselves, who haveaccessed the Aristya Silver comapany’s website (http://www.aristya-silver.com).Samples have been determinded by using a metode called purposive sampling. Thesamples, moreover, have been chosen by 200 people. Hypotheis has been observedusing Structural Equation modelling (SEM) with an istalled application tool calledanalysis of Moment Structure (AMOS) version 18. The result of the research showsthat: (1) the service and quality of the E-commerce website significant positivelyeffects the consumers’ satisfaction. (2) the satisfaction significant positively effectsupon the loyalty. (3) the service and quality of the E-commerce website significantpositively effects the consumers’ loyalty. (4) There’s indirect connection betweenexogenous variabel (E-servqual) and endogenous variabel (behavioral loyaltyintentions) through interviening variabel which is consumer’s satisfaction. Thisalso interpreted that consumer’s satisfaction hasn’t intervene behavioral loyaltyintention.